Elaboration of boehmite nano-powders by spray-pyrolysis - Caiut, J. M. A. [UNESP]; Dexpert-Ghys, J.; Kihn, Y.; Verelst, M.; Dexpert, H.; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (Elsevier B.V. Sa, 2009)
Boehmite (gamma-AlOOH) synthesis have been investigated using a spray pyrolysis (SP) device starting from a stable sol of Al-tri-sec-butoxide peptized by nitric acid. Free spherical particles from 100 to 500 nm have been elaborated. Particles sub-structure is made of nano-crystalline boehmite with very small average crystallite size (one crystal cell along the b axis). The nano-crystalline boehmite synthesized by SP at low temperature (200 degrees C) is spontaneously dispersible in water without any surface treatment. Boehmite powder may be transformed to transition gamma-alumina by heat post-treatment. Powders of sub-micrometric and spherical gamma-alumina particles may also be synthesized by SP at 700 degrees C. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Spray-pyrolysis; Nano-powders; Boehmite; Alumina; Sol-gel